PEPSIN DIGESTION OF RABBIT AND SHEEP ANTIBODIES : THE EFFECT ON COMPLEMENT FIXATION - Schur, Peter H. (The Rockefeller University Press, 1963)
7S sheep antibody is similar to 7S rabbit antibody, insofar as it too can be digested with pepsin to yield a 5S fragment still capable of precipitating homologous antigen. The 5S fragment from rabbit as well as sheep antibody is capable of fixing guinea pig complement. However, this fixation differs from the fixation by 7S antibody, since preformed antibody-antigen aggregates containing either sheep or rabbit 5S antibody fix only a maximum of 20 to 40 per cent of the total complement. The portion of complement which is fixable by the 5S preformed aggregates seems to be different from the remainder of the complement. Prior treatment of guinea pig serum with 5S washed preformed aggregates removes that portion of complement fixable by 5S antibody, and will leave the complement remaining unable to be fixed by further addition of 5S immune aggregates. Such absorbed complement, however, is as capable as is unabsorbed complement of being fixed by 7S antibody. The 5S sheep and rabbit antibody fixes the portion of complement which it is capable of fixing, as well as or better than the corresponding 7S antibody fixes the total complement. 5S preformed aggregates are broken down by treatment with cysteine, and their complement-fixing ability is lost.